Problematika sodnega določanja in zakonske regulacije zaposlitvenega statusa Uberjevih voznikov - Polajžar, Aljoša (Delavci in delodajalci, 2023)
In this paper, we analyse certain aspects of the legal, philosophical and sociological issues of judicial determination or legislative regulation of the (unclear) employment status of Uber drivers – in the light of judicial and legislative examples from the UK and the USA. In doing so, we note that both approaches (statutory regulation or judicial determination of employment status) carry certain problems that must be taken into account when approaching the regulation of the platform economy.
Keywords: casuistic regulation; employment status; judicial decision-making; legal principles; platform work; prevoz; spletne storitve; subordination; Uber; zaposlitveni status